Aplikasi Building Information Modeling (BIM) Menggunakan Software Tekla Structuresx 2022 Pada Konstruksi Gedung Puskesmas Arjasa, Kabupaten Sumenep, Jawa Timur - Wijaya, Handika Setya; Sa’dillah, M.; Elsa, Yustina Roslani Nona (Universitas Nahdlatul Ulama Blitar, 2024)
In the construction sector, progress in the development of information technology is very rapid, providing many benefits for construction work that has a level of difficulty and complexity in the work process, including the field of AEC (Arobitect Engineering Construction). The data used in this research are primary data and secondary data from the project at the Arjasa health center building project, Sumenep Regency, East Java. Data collection was carried out quantitatively. This data will later be used in modeling using Tekla Stuctures 2022 software. Based on the case study, 3D modeling is carried out starting from the process of making grids, elevations, foot plate and continuous foundations, sloofs, columns, beams and roofs, followed by 4D modeling or Time Schedule where the schedule the work that has been entered into the task manager is then processed using project visualization, and the last is 5D modeling or cost estimation using Tekla Structures 2022 software. Modeling is done by taking the volume results obtained from 3D building modeling using Tekla Structures 2022 software and then calculating it using Excel. The RAB results obtained for the Polyclinic Building were IDR 224,175,887.47 and for the IGD building IDR 214,707,268.24.